Implementasi Kebijakan Sistem Zonasi Penerimaan Peserta Didik Baru (PPDB) di Sekolah Menengah Pertama Negeri 4 Waru: (Studi Analisis Kebijakan Publik) - Sugeng Iswahyudi; Aris Sunarya; Sri Kamariyah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The zoning system policy in the New Student Enrolment (PPDB) is an educational policy reform aimed at equalising access to services and improving the quality of education in Indonesia. This research analyses the implementation of the PPDB zoning system policy at the level of State Junior Secondary Schools using George C. Edward III's policy implementation theory approach, which covers four main variables: communication, resources, disposition, and bureaucratic structure. The research method employs a qualitative approach with a descriptive research type. Data collection techniques were conducted through in-depth interviews, observation, and documentation study of the regulations implementing the zoning system policy. The findings show that the implementation of the PPDB zoning system policy has proceeded in accordance with the technical regulations of Permendikbud Number 01 of 2021 and Sidoarjo Regent Regulation Number 37 of 2020. The admission routes provided include the zoning route, achievement, affirmation, and parental transfer, which offer fair opportunities for all prospective students. Nevertheless, there are still obstacles in the execution, particularly related to the limited infrastructure for distance learning, public perception regarding the selection mechanism, and the disparity between the number of available places (quota) and the number of applicants for certain routes. This research recommends the need for more comprehensive socialisation, improvement of supporting infrastructure, and periodic evaluation of policy implementation to ensure the achievement of the goal of equitable and quality education.